2000
DOI: 10.1034/j.1600-0846.2000.006003128.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the physical properties of the stratum corneum by a new tactile sensor

Abstract: BACKGROUND/AIMS: The physical properties of the stratum corneum (SC) change with its water content, which is regulated by the presence of water solutes (natural moisturizing factors) and lipids in the SC, and are considered to be responsible for the induction of desquamation, skin surface roughness, and fine wrinkles. Recently a new type of tactile sensor developed for evaluating the physical properties of objects has been introduced as a simple, non-invasive method to evaluate them; because the data obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 16 publications
0
21
0
Order By: Relevance
“…When the probe contacts softer objects, a lower Df value is obtained. Lindahl et al (1998) found Df suitable for evaluating skin stiffness, since Df is correlated to spring constant k. More recently, Sakai et al (2000) reported that the Df value obtained with the Venustron tactile sensor at a pressure of 2 g was significantly correlated with the SC hydration state. The Venustron tactile sensor, however, has been confirmed to measure the stiffness of not only the SC but also the dermis in the face (Sakai et al, 2000).…”
Section: Methodsmentioning
confidence: 96%
“…When the probe contacts softer objects, a lower Df value is obtained. Lindahl et al (1998) found Df suitable for evaluating skin stiffness, since Df is correlated to spring constant k. More recently, Sakai et al (2000) reported that the Df value obtained with the Venustron tactile sensor at a pressure of 2 g was significantly correlated with the SC hydration state. The Venustron tactile sensor, however, has been confirmed to measure the stiffness of not only the SC but also the dermis in the face (Sakai et al, 2000).…”
Section: Methodsmentioning
confidence: 96%
“…Amino acids were analyzed using a Hitachi Amino Acid Analyzer L-8800 as described previously (22). Ionic content was analyzed using ion chromatography IC-8010 (TOSOH, Tokyo, Japan) and Shodex packed column HPLC YK-421 (Showa Denko, Tokyo, Japan) using 3 mM phosphate buffer at 1 ml/min flow.…”
Section: Methodsmentioning
confidence: 99%
“…The design of the sensor probe and the signal analysis were also developed [4], leading to a simultaneous, continuous force and area measurement which reduced errors and increased sensitivity. Another resonance sensor system, Venustron Ò , has been developed and used to measure the physical properties of skin [19]. The sensor is computer-controlled and samples the change in frequency and the force exerted on the sensor during impression into an object.…”
mentioning
confidence: 99%